The correlation of upper airway abnormalities with obstructive sleep apnea syndrome in young adult - Kanti Yunika; Febby Mardalita; Sefri Noventi; Dwi Marliyawati; Muhamad Thohar Arifin (DiscoverSys Inc., 2020)
Background: Obstructive Sleep Apnea Syndrome (OSAS) is one of sleep disorder characterised by repeated episodes of total obstruction in the upper airway system during sleep. The incidence of OSAS is estimated to be 1-10% of general population. OSAS can be affected by several risk factors. One of risk factor of OSAS is upper airway abnormalities. The study aims to find out the association between individual risk factor including septum deviation, nasal turbinate hypertrophy, tonsillar hypertrophy and mallampati score with the incidence of OSAS in young adults.Methods: Analytic observational research with case-control design was carried out on young adults aged 18-23 years in the city of Semarang during May - September 2018 grouped into OSAS and non-OSAS based on Polysomnography (PSG), then history and physical examination were performed. Statistical tests were using chi-square, Fisher's exact test, and logistic regression.Result: Total of 22 people were included in OSAS group and 22 were included in the control group. Bivariate analysis showed septum deviation (p= 0.005), tonsillar hypertrophy (p=0.015) and mallampati score (p<0.001) significantly related to the incidence of OSAS, whereas nasal turbinate hypertrophy was not associated with OSAS incident. The results of multivariate analysis found that BMI had an OR value of 133 (95% CI 12.726 – 1390.002, p<0.001) independently associated with the occurrence of OSAS in young adults.Conclusion: Septal deviation, tonsillar hypertrophy, mallampati score are the risk factors for OSAS in young adults.